Gyula Lux, the Linguistand the Pedagogue - Bencéné Fekete, Andrea (Acta Scientiarum Socialium, 2011)
Gyula Lux, the Linguist and the Pedagogue. Until nowadays there was no analysing work made about the methodology, pedagogy and linguistics of Gyula Lux and the education of languages in the 1920s. In my study I would like to introduce my language-educational, historical research. The principal aim of my work is to present the work of Gyula Lux. I would like to exhibit the first – and the longest – working-period of Gyula Lux, the reforming ambitions of the 1920s and the new methods in educating foreign languages. I analysed the books, publications written by Gyula Lux in the field of methodology. I focused on the education of languages and its location in the taxonomy of sciences. To reveal the work of Gyula Lux genuinely, it is crucial to assay the history of education, the cultural policy, education policy of the era in focus, and introduce the theory of curriculum, that meant the basis of my researches. Furthermore I revealed the history of the College of Teachers for Educating German Minorities, from the beginning to the end. I also made researches of the history of a settlement in the area of minorities, called Dobsina. I present the procedure of German language appearing in the Hungarian culture, and the changes in the language-policy, that was a crucial changing point in the Hungarian educational policy, thanks to Kunó Klebelsberg. As most of the work of Gyula Lux consists of language-pedagogy, I put emphasis on this area in my work. I revealed the theoretical background of language education in the 1920s. Within this field I schemed the didactical changes in the period that had huge effect on the curriculum of the education of foreign languages. I unfolded the linguistic trends in the background of the era’s methodology and the theories remounting to that period. I introduced the exhibition of the exercise books of Gyula Lux by the critics of the language books used previously, then compare them with his new-born methods. His methodology is specific, as he edited his books and reformed the Gouin-method by using a psychological trend and taking the psychology of children into account. I demonstrate the appearing types of texts in the books with the help of diagrams.
Keywords: Gyula Lux; history of language education; Kunó Klebelsberg